WORD FORMATION PROCESSES ON JARGON USED BY COFFEE CORNER BARISTA FOR INDONESIA LATTE ART CHAMPIONSHIP IN TERMS OF PEDAGOGICAL UNIT - PUTRI, AMELIA PERMATA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: word formation processes, jargon, Coffee Corner, barista, Indonesia Latte Art Championship, pedagogical.Language  always develops  day by day, this development influences many factors and aspects in language itself include pedagogical unit. Language, human and society are inseparable, different background of many aspects influence how they use their language to show their society. Some of  the occupation fields also create their own language and vocabulary to help them doin their daily activities. One example is the increasing number of coffee shopexistence that give effect to the number of barista occupation. In this study thewriter is interested in analyzing  both of the jargon and the word formation processes that were used by barista. This study is aimed at analyzing the jargon, word formation processes, and the meaning of the jargon used  by Coffee Corner barista for their Indonesia Latte Art Championship 2014.This study is using the descriptive qualitative approach. The writer only focused analyzing the  jargons that were used by four baristas who work in the Coffee Corner from  October to November 2014.From the results of this study, the writer found that there were 68 (sixty eight) jargons. The jargon were analyzed  based on the theory about sociolinguistic and related it with the morphological process. Those 68 (sixty eight) jargons underwent seven word formation processes. There are blending, borrowing, coinage, compounding, acronym, derivation, and multiple processes. The writer also consulting the result with the Coffee Cupper’s Handbook (2001).The writer suggest the next researcher who is interested in sociolinguistics and word morphological language with same topics will analyze it with another field that is happening in the society and relate it with the pedagogical unit. The writer also hopes that this study will give contributions to the English Education Study Program as the references to analyzed about Word Formation Processes onJargon Used by Coffee Corner Barista for Indonesia Latte Art Championship InTerms of Pedagogical Unit.